Feasibility of clinical newborn metabolic screening in a high-volume maternity center in Nepal - Janine Y. Khan; Kalpana U. Subedi; Shailendra B. Karmacharya; Prajwal Paudel; Dharma S. Manandhar; Rose Hennessy Garza; Keith A. Dookeran; Sunil R. Manandhar (BMC, 2024)
Abstract Background Strategic action plans around newborn health evaluation are needed, to address the high neonatal mortality rate in Nepal. Surveillance systems, like Newborn Metabolic Screening (NBS), could reveal unrecognized drivers of neonatal death. NBS is not routinely performed in Nepal. Our objective was to determine the feasibility of establishing NBS, and its acceptability among healthcare providers and parents, in Nepal. Methods This prospective cohort study was conducted between November 2021 and May 2022 in term/late preterm infants born at Paropakar Maternity Hospital, Kathmandu, screening for 6 disorders that can be confirmed and managed locally. Staff were trained on dried-blood spot collection and transport protocols, performance metrics were established, and assays were performed at an accredited laboratory in Bangalore, India. Surveys were developed to determine acceptability among health-care providers and parents. Results Of 835 parents approached for the study, 825 (98.8%) consented. Parental surveys showed that 92% considered "no cost" option most important in choosing to participate in the study. Samples were transported to laboratories in Kathmandu and Bangalore in 36 ± 24 h, and 4.75 ± 1 days, which exceeded expected metrics of 24 and 48 h, respectively. Results were communicated to parents by 9.5 ± 2 days, which was within the expected metric window of 14 days. Abnormalities were reported in 13 infants and included 5 hemoglobinopathy traits (4 Hb E and 1 Hb D), 3 congenital hypothyroidism, 2 glucose-6-phosphate dehydrogenase deficiency, 1 congenital adrenal hyperplasia, 1 elevated acylcarnitine, and 1 biotinidase deficiency. Healthcare providers surveyed (n = 116) showed that 67% reported a moderate understanding of NBS; all indicated that screening would be beneficial. Most cited early diagnosis and treatment, as well as, providing risk to future pregnancies as significant benefits. 90% thought screening should be routinely performed. Conclusions We demonstrate that it is feasible to introduce NBS in Nepal. Transport metrics were longer than expected due to COVID pandemic travel restrictions; however, it was possible to deliver results to families within 2 weeks of birth. Parents overwhelmingly considered "no cost" option as the most important in choosing to screen. A government-sponsored program will be a key factor in establishing NBS in Nepal.